(untitled) (IAHS Medical Journal, 2024)
Background: In addition to individuals with elevated androgen levels, female pattern hair loss is also reported in women without elevated androgen levels. In recent years, vitamin D and ferritin levels have been taken into account while treating these individuals.Women who have female-pattern hair loss may also suffer from vitamin D and iron deficiencies. This research is to determine the roles that ferritin and vitamin D play in the etiopathogenesis of hair loss. Materials and methods: A cross-sectional study was conducted in Delta Medical College and Hospital among the 50 female patients aged between 12-58 years. Results: According to the findings of our research, a total of 89% of the female patients had blood vit-D levels that were both deficient and insufficient level, which indicates that deficiency of Vit-D can enhance the hair loss in female patients. Also, the ferritin value was quite deficient in range among the participants. Conclusion: This study had a small sample size, was conducted in just one site, and didn’t use a standardized method to examine the dietary intake of FPHL patients. For this reason, it is recommended that, in addition to other hormonal tests, blood D3 levels and other mineral tests be analyzed to assess a patient’s health. IAHS Medical Journal Vol 6(1), June 2023; 3-5